Kebijakan Kriminalisasi Perbuatan Curang oleh Advokat dalam RUU KUHP (The Policy on Criminalization of Fraudulent Acts by Advocates in the Criminal Code Bill) - Prianter Jaya Hairi (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2020)
The idea of criminalization of fraudulent acts by advocates in the judicial process has received public attention, especially from advocates. The criminal law norms regarding fraudulent acts by advocates in the Criminal Code Bill (CCB) raise many questions from the point of view of the criminalization policy. This study aims to analyze the criminalization policy against these acts in the CCB. This study is a juridical-normative study with descriptive-analytical methods. The discussion concluded that fraudulent acts by advocates in the form of “playing two feet” and actions “influencing parties in the law enforcement process with or without compensation” are actions that are not following the fundamental values prevailed by the public and also considered punishable. This arrangement aims to protect clients who request legal assistance services. The formulation of this regulation then becomes regulated to complement the criminal law norms related to the existing advocate profession. However, from the aspect of offense formulation, there are still things that need to be addressed so as not to cause multiple interpretations during its implementation, especially in relation to Article 282 of the CCB. AbstrakGagasan mengenai kriminalisasi terhadap perbuatan curang oleh advokat dalam proses peradilan mendapat perhatian masyarakat, terutama dari kalangan advokat. Norma hukum pidana mengenai perbuatan curang oleh advokat dalam RUU KUHP menimbulkan banyak pertanyaan dari sudut pandang kebijakan kriminalisasi. Kajian ini bertujuan untuk menganalisis kebijakan kriminalisasi terhadap perbuatan tersebut dalam RUU KUHP. Kajian ini merupakan penelitian yuridis-normatif dengan metode analisis yang bersifat deskriptif analitis. Pembahasan di antaranya menyimpulkan bahwa perbuatan curang oleh advokat dalam bentuk perbuatan “main dua kaki” dan perbuatan “mempengaruhi pihak-pihak dalam proses penegakan hukum dengan atau tanpa imbalan” merupakan perbuatan yang tidak sesuai dengan nilai-nilai fundamental yang berlaku dalam masyarakat dan dianggap oleh masyarakat patut untuk dihukum. Pengaturan ini bertujuan untuk melindungi klien yang meminta jasa pendampingan hukum. Rumusan pengaturan ini kemudian menjadi diatur untuk melengkapi norma hukum pidana terkait profesi advokat yang ada selama ini. Namun dari aspek formulasi delik, masih ada yang perlu dibenahi agar tidak menimbulkan multitafsir saat penerapannya, khususnya terkait dengan Pasal 282 RUU KUHP.